2022
DOI: 10.3389/fmicb.2021.805472
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay Between Coronavirus and Type I IFN Response

Abstract: In the past few decades, newly evolved coronaviruses have posed a global threat to public health and animal breeding. To control and prevent the coronavirus-related diseases, understanding the interaction of the coronavirus and the host immune system is the top priority. Coronaviruses have evolved multiple mechanisms to evade or antagonize the host immune response to ensure their replication. As the first line and main component of innate immune response, type I IFN response is able to restrict virus in the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 224 publications
(247 reference statements)
0
13
0
Order By: Relevance
“…During this process, it was reported that SARS-CoV-2 encoded at least 14 proteins, accounting for about half of the total proteins encoded by the virus, to interfere with IFN production [ 88 90 ]. These proteins include the structural membrane (M), nucleocapsid (N) proteins, the accessory proteins (3, 6, 8, and 9b), and the nonstructural proteins (NSP1, 3, 5, 6, 12,13, 14, and 15) generated from a large open reading frame (ORF) encoding 1ab by papain-like proteinase (NSP3, NLpro) and 3C-like proteinase (NSP5, 3CLpro) -mediated cleavage.…”
Section: Targeting the Type I Ifn Production By Sars-cov-2mentioning
confidence: 99%
“…During this process, it was reported that SARS-CoV-2 encoded at least 14 proteins, accounting for about half of the total proteins encoded by the virus, to interfere with IFN production [ 88 90 ]. These proteins include the structural membrane (M), nucleocapsid (N) proteins, the accessory proteins (3, 6, 8, and 9b), and the nonstructural proteins (NSP1, 3, 5, 6, 12,13, 14, and 15) generated from a large open reading frame (ORF) encoding 1ab by papain-like proteinase (NSP3, NLpro) and 3C-like proteinase (NSP5, 3CLpro) -mediated cleavage.…”
Section: Targeting the Type I Ifn Production By Sars-cov-2mentioning
confidence: 99%
“…They are currently classified into three groups: Type I, II, and III. Type I IFNs consist of IFN-α, IFN-β (also IFN-δ, IFN-ε, IFN-κ, IFN-τ, IFN-ω, and IFN-ζ) but also within Type II is IFN-γ, whilst type III IFNs encompass IFN-λ [77] Noteworthy, studies indicate that with MERS and RSV that timing of Type I IFN production affects this [59,60]. With regards to SARS-CoV-2 sensitivity to IFN, early case studies indicate SARS-CoV-2 sensitivity to IFN-α and IFN-β in vitro, however more recent tissue studies indicate that IFN-α, IFN-β response may paradoxically facilitate the propagation of COVID-19 from the respiratory epithelium to the vasculature through direct endothelial cell infection [78,79].…”
Section: V) Role Of Toll-like Receptors (Tlr) or Tlr Induced Ifn Dysr...mentioning
confidence: 99%
“…They are currently classified into three groups: Type I, II, and III. Type I IFNs consist of IFN-α, IFN-β (also IFN-δ, IFN-ε, IFN-κ, IFN-τ, IFN-ω, and IFN-ζ) but also within Type II is IFN-γ, whilst type III IFNs encompass IFN-λ [75] Noteworthy, studies indicate that with MERS and RSV that timing of Type I IFN production affects this [57,58]. With regards to SARS-CoV-2 sensitivity to IFN, early case studies indicate SARS-CoV-2 sensitivity to IFN-α and IFN-β in vitro, however more recent tissue studies indicate that IFN-α, IFN-β response may paradoxically facilitate the propagation of COVID-19 from the respiratory epithelium to the vasculature through direct endothelial cell infection [76,77].…”
Section: V) Role Of Toll-like Receptors (Tlr) or Tlr Induced Ifn Dysr...mentioning
confidence: 99%